2022
DOI: 10.6007/ijarped/v11-i1/11959
|View full text |Cite
|
Sign up to set email alerts
|

Industries and Vocational Training Centres Partnership: Issues and Improvement Plan

Abstract: Several challenges have been found to develop and sustain collaboration between industries and vocational institutions, including funds, misunderstanding of objectives, policy limitation, and bureaucracy. This paper systematically reviewed five journals regarding the issues in collaboration between industries and vocational institutions, then identified a possible solution to improve that collaboration. A meta-analysis reviewed conducted on five related journals and research papers concerning cooperative relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…The students' experiential learning from the industrial trainer opened their minds on new relevant knowledge as it relates to skills in EIMT. This corroborates similar findings reported that the industry role is crucial to channel information on the latest technology used by the industry through collaborative partnership arrangements to produce work ready graduates (Mustafa et al, 2022). Another important revelation made in the study was the updating of the teacher's knowledge whilst the industry employer was teaching.…”
Section: Development Of New Relevant Trade-related Knowledgesupporting
confidence: 91%
See 4 more Smart Citations
“…The students' experiential learning from the industrial trainer opened their minds on new relevant knowledge as it relates to skills in EIMT. This corroborates similar findings reported that the industry role is crucial to channel information on the latest technology used by the industry through collaborative partnership arrangements to produce work ready graduates (Mustafa et al, 2022). Another important revelation made in the study was the updating of the teacher's knowledge whilst the industry employer was teaching.…”
Section: Development Of New Relevant Trade-related Knowledgesupporting
confidence: 91%
“…Collaboration involving TVET training colleges and the business enterprise has become a necessity in the production of human capital that is needed to transform any given economy. In the era of the fourth industrial revolution, the latest skills and technology developments are needed to ensure the success of any TVET institution in the production of highly competent graduates that satisfies industrial requirements (Mustafa et al, 2022). Thus, such partnership between business and TVET institutions is a mechanism in developing and strengthening the vocational education system, especially in the production of work-ready graduates through empowerment in technical skills technology as well as increased employability (Mustafa et al, 2022).…”
Section: Industry Stakeholder and Tvet Institution Collaborationsmentioning
confidence: 99%
See 3 more Smart Citations